Solving the powerpoint predicament : using digital media for effective communication - Bunzel, Tom (Que, 2006)
Solving the PowerPoint Predicament Using Digital Media for Effective Communication Don't Just Present: Inspire! Everyone uses PowerPoint, but how effective is your presentation at meeting the goals you've outlined? A great presentation is more than just a slideshow-it's about using PowerPoint to its maximum potential to get your message across to your audience. That's the PowerPoint Predicament. Tom Bunzel reveals how to conceive, plan, develop, and deliver truly effective business, academic, and inspirational communications, not just PowerPoint slideshows. Discover how to motivate your audience by: Getting beyond bullet points to tell a story that touches your audience at the deepest levels Mastering proven principles of effective communication Planning, organizing, and designing every presentation for maximum impact Making sure every word, image, effect, and slide exists for a good reason Creating charts and diagrams that instantly make your point Using animation, navigation, video, and audio to drive home your message, not distract from it Avoiding mistakes that lead to boring presentations: no more "death by PowerPoint" Building Web and self-running kiosk presentations that really work Leveraging the rest of Microsoft Office to create even better presentations Using third-party add-ons to communicate with PowerPoint even more effectively: video capture, flowcharting, DVD authoring, rehearsal, and more When you present, you're on the line: your credibility, your career, your future as a leader. Use your software and imagination to its full potential-with this book! Covers PowerPoint 2007, 2003, XP, 2000, 99, and 97- for Windows or Mac PowerPoint users Tom Bunzel is a leading presentation expert. He has appeared on Tech TV's "Call for Help," was a featured speaker at InfoComm and PowerPoint LIVE, and has served as a technology coach for companies ranging from Iomega to the Neuroscience Education Institute, where he provided personal PowerPoint instruction to physicians. He offers live seminars via streaming media, and he has been published in Presentations Magazine. His books include Sams Teach Yourself PowerPoint 2003 in 24 Hours and Digital Video on the PC. He updated the Visual QuickStart Guide to PowerPoint 2002/2001 for Windows and Mac. The book companion CD-ROM contains numerous PowerPoint presentations and other examples from the book, two sample chapters from Cliff Atkinson's Beyond Bullet Points: Using Microsoft PowerPoint to Create ...